2006
DOI: 10.1089/ten.2006.12.625
|View full text |Cite
|
Sign up to set email alerts
|

Can Mesenchymal Stem Cells Survive Under Normal Impaction Force in Revision Total Hip Replacements?

Abstract: Impaction allograft as a scaffold for bone-forming cells is a tissue-engineering approach for filling bone defects that are commonly encountered during revision total joint replacement (THR). The purpose of this in vitro study is to assess the viability of mesenchymal stem cells (MSC) grown on allograft following impaction using forces similar to those measured during revision total hip replacements. Impaction forces of 0, 3, 6, and 9 kN were used representing normal and high impact. The results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, the viability and function of the cells were not severely affected by exposure to temperatures up to 48°C for 150 seconds; all six tests we used agreed that after 7 days these cells showed signs of growth and metabolic activity, as seen in the control sample, that were typical of hMSCs in culture. Interestingly, all of the samples up to this point, including the control group, showed evidence of the lag phase of cell growth typically between 2 and 3 days after heat treatment [17] shown by alamarBlue™ analysis of cell metabolic activity, which gives a proportional indication of cell number [28]. During these days some of the cells possibly died in culture, with the remaining cells each exhibiting a higher metabolic level, before exponential growth in cell number after 3 days; this hypothesis is reinforced by the Trypan Blue exclusion dye experiment, in which the 48°C/80 seconds and 48°C/150 seconds groups showed signs of a recovery in the cell number in culture after 3 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the viability and function of the cells were not severely affected by exposure to temperatures up to 48°C for 150 seconds; all six tests we used agreed that after 7 days these cells showed signs of growth and metabolic activity, as seen in the control sample, that were typical of hMSCs in culture. Interestingly, all of the samples up to this point, including the control group, showed evidence of the lag phase of cell growth typically between 2 and 3 days after heat treatment [17] shown by alamarBlue™ analysis of cell metabolic activity, which gives a proportional indication of cell number [28]. During these days some of the cells possibly died in culture, with the remaining cells each exhibiting a higher metabolic level, before exponential growth in cell number after 3 days; this hypothesis is reinforced by the Trypan Blue exclusion dye experiment, in which the 48°C/80 seconds and 48°C/150 seconds groups showed signs of a recovery in the cell number in culture after 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study investigated the effect of the forces generated during impaction allograft in revision total hip replacement on the viability of hMSCs; the cells were found to withstand these forces [17]. The current study investigated the heat generated as a single factor that may affect the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in sheep have demonstrated significantly better bone formation around hip implants compared with HA alone [89]. Furthermore, a number of studies have demonstrated that MSCs can successfully withstand the force associated with impaction allografting and would therefore potentially be of use in this manner to treat pelvic bone loss in revision arthroplasty [90,91].…”
Section: Use In Arthroplasty Surgerymentioning
confidence: 99%
“…The mechanical force was observed to play an important role in directing stem cell fate toward osteogenic, chondrogenic and myogenic lineages in MSCs [6]. Among the various mechanical forces, compressive loading [11,12,13], shear stress [14,15] and tensile stress [16,17] are commonly used as the bio-mimetic loadings that are related to physiological environment such as blood vessel and bone tissue. However, few studies are devoted to the investigation of tensile strain in guiding MSCs in proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%